Nanomateriais - o que são, que riscos comportam - Pinto, Fátima (2021)
Aula 6: Nanomateriais - o que são, que riscos comportam. Nanomaterials (NM) – Materials with one or more components that have at least one dimension in the range of 1 to 100 nm